Intergeneration correlation and parent-offspring regression in rust resistance derived F4 and F5 generations in bread wheat - REENA RANI; VIKRAM SINGH; M S PUNIA (The Indian Journal of Agricultural Sciences, 2021)
The present investigation aimed to determine the intergeneration correlation and parent-offspring regression in F4 and F5 generations of two wheat crosses, WH 1105 × WH 711 and RAJ 3765 × WH 711 grown during the rabi 2015-16 and 2016-17 in research area of Wheat and Barley Section, CCS HAU, Hisar. Correlation studies indicated that grain yield/plant showed a significant positive correlation with almost all the yield attributing traits which may be considered as prime traits during selection. Biological yield/plant had the highest positive direct effect on grain yield/plant, followed by the harvest index. Almost all the characters had high indirect effects through biological yield/ plant and harvest index. The F4 generation progenies showed highly significant and positive values of intergeneration correlation and regression with F5 generation progenies for all the characters in both the crosses. Therefore, the performance of the plants in the F4 generation is a reliable indicator of the performance of their progeny in subsequent generations. Narrow sense heritability values were high for the number of grains/ear, grain weight/ear and grain yield/ plant while response to selection values were high for the number of grains/ear, biological yield/plant, plant height and number of spikelets/ear in the progenies of both crosses. Hence, improvement through selection can be based upon these traits in these crosses. Thus estimation of correlation and regression analysis among yield and yield components may provide effective selection criteria to improve wheat grain yield.